2022
DOI: 10.3390/min12030301
|View full text |Cite
|
Sign up to set email alerts
|

Clays and Clay Minerals in the Construction Industry

Abstract: Clay is a naturally occurring material that can be converted to different clay minerals through thermal treatments, and can be used for the development of different products. Clays and clay minerals have been used for different applications in different sectors. Detailed information regarding the applications of these materials in the construction industry are described. Clay has been used as a supplementary cementitious material in Portland cement (OPC) mortars and concretes. These minerals decrease raw mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 89 publications
0
25
0
Order By: Relevance
“…A plausible explanation is the initial dense microstructure changes during sintering, resulting from the thermal decomposition of carbonates, sulfates, and organics in clays while sintering. 28,29 In conclusion, P18 is considered the optimized ceramic formula, and the optical images of the as-prepared large-sized porcelain thin ceramic tile derived from the P18 formula are shown in Figure 5. This demonstrates that the flux formula optimization process employed in this study is fully compatible with standard ceramic industry practices.…”
Section: Optimization For Formula Regionsmentioning
confidence: 99%
“…A plausible explanation is the initial dense microstructure changes during sintering, resulting from the thermal decomposition of carbonates, sulfates, and organics in clays while sintering. 28,29 In conclusion, P18 is considered the optimized ceramic formula, and the optical images of the as-prepared large-sized porcelain thin ceramic tile derived from the P18 formula are shown in Figure 5. This demonstrates that the flux formula optimization process employed in this study is fully compatible with standard ceramic industry practices.…”
Section: Optimization For Formula Regionsmentioning
confidence: 99%
“…Clay is used in different industrial sectors such as construction, ceramics, pharmaceuticals, environmental remediation, conservation of historical mortars, etc. [6][7][8]. The choice of clay depends on its properties and cost.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the aforementioned characteristics serve as the cornerstone for the socioeconomic growth and sustainability of small-scale and artisanal clay mining industries in emerging nations (Diko-Makia and Ligege 2020). Clays are widely distributed in practically every nation (Singh 2022). Clay minerals rank among the world's most significant and practical industrial minerals.…”
Section: Introductionmentioning
confidence: 99%